Analysis of Mechanical Properties and Slope Stability of Red Bed Soft Rock: A Case Study in Xinjiang Irrigation Diversion Channel - Da Liu; Jianglin Gao; Fang Chen; Songtao Hu; Xiaohua Zhao; Yan Li (Advances in Civil Engineering)
The channel slope in the red-bed soft rock area is prone to instability and collapse due to the influence of the channel flow movement, rainfall, weathering, and other factors. Under long-term operation conditions, the sediment stripped from the channel side wall is liable to silt along the process of water flow transportation in the channel, which seriously leads to elevation of the channel bottom, increase of channel width, and reduction of the horseway, which affect the normal water conveyance and operation safety of channels. In view of the collapse and instability of Zhetang diversion irrigation channel project in Xinjiang hydraulic project, through on-site sampling and indoor rock mechanics test, the strength mechanical parameters of slope rock samples are obtained, and the indoor rheological test is carried out, and the triaxial rheological law is obtained. Under different levels of stress, the axial creep strain accounts for more than 50% of the total axial strain, indicating that the rheological effect of sample rock is obvious. Based on the strength parameters of rock samples, a numerical model is established. The stability of red-bed soft rock channel bank slope is studied by using the strength reduction method of finite element method. The seepage field of channel slope under conventional working conditions is analyzed, and the slope stability under different operating conditions is compared and calculated. The results show that the slope stability safety factor of Zhetang diversion irrigation channel slope is 1.60 under conventional working conditions and 1.33 under check working conditions, which are greater than the recommended value in the specification.